2016
DOI: 10.7903/cmr.14796
|View full text |Cite
|
Sign up to set email alerts
|

Customer Perception of Green Advertising in The Context of Eco-Friendly FMCGs

Abstract: Past studies have focused on the role of advertising in consumer behaviour. However, with the emergence of green marketing as a field of study, there is a growing importance in eco-friendly products. The present study contributes to the literature on green marketing by investigating Australian customers' exposure to and trust in green advertising in the context of eco-friendly Fast Moving Consumer Goods. In addition, the study investigates whether customers' purchase intentions are influenced by such advertise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…This is a qualitative research, which focuses on the experiences of individuals and the meanings that are attached to these experiences, in particular, the way in which the individual understands experiences and interprets the social world (Creswell et al , 2007). The qualitative approach permits participants in a study to address a topic or phenomenon in their own terms rather than within a framework constructed by the researcher (Hollensbe et al , 2008). Qualitative methods are particularly effective in providing insights into sense-making of the world and provide valuable insights via encouraging people to reflect on lived experiences (Luzio and Lemke, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…This is a qualitative research, which focuses on the experiences of individuals and the meanings that are attached to these experiences, in particular, the way in which the individual understands experiences and interprets the social world (Creswell et al , 2007). The qualitative approach permits participants in a study to address a topic or phenomenon in their own terms rather than within a framework constructed by the researcher (Hollensbe et al , 2008). Qualitative methods are particularly effective in providing insights into sense-making of the world and provide valuable insights via encouraging people to reflect on lived experiences (Luzio and Lemke, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The key aim of the investigator was to encourage respondents to disclose their insights to enhance the reliability of the interview process and the importance of the data result. Regardless of the relaxed style, semi-structured questions permit the researcher to uphold emphasis on the subject at a suitable pace during the course of the interview discussions (Hassan and Valenzuela, 2016). All interviews were recorded using a cell phone recorder.…”
Section: Methodsmentioning
confidence: 99%
“…This is in agreement with a study by Khandelwal & Bajpai (2011) where no significant linear impact was found between attitudes towards green ads and purchase intention for green products. A low percentage of customers (29.6%) reported the influence of ads regarding eco-friendly products in a study investigating the relationship between customer trust and green ads (Hassan & Valenzuela, 2016). In the same study, only 15% of respondents developed complete trust of the aforementioned ads and the conveyed messages.…”
Section: Discussionmentioning
confidence: 93%